Alternative Use of Breadfruit Flour as a Partial Substitute for Wheat Flour in Making Scones - Kamila, Shabrina; Novianti, Selvi; Arifin, Djauhar (Politeknik Pariwisata NHI Bandung, 2024)
Purpose: This research aims to analyze the influence and differences between scones using breadfruit flour as partial substitution of wheat flour and scones using full wheat flour on the appearance, texture and flavor. Furthermore, to find out the best formula of breadfruit flour substitution in the making of scones which has the most likeliness for the consumers. Design/Methodology/Approach: This research was carried out using quantitative approach with data collection through literature study, observation and hedonic test. Experimental methods carried out 3 formula of experiments with 3 different percentages, namely 30%, 50% and 70% breadfruit flour substitution to wheat flour. The hedonic test was given to 30 untrained panelists with random selection. Findings: The research results shown that formula which has the most likeliness is scone with maximum of 30% breadfruit flour substitution. Research limitations/conclusions: The limitation of this research is the limited data and information about scones because scones are still rarely discussed in various journals or other literature, so the reliance was only on a few books and secondary data that came only from previous literature studies. Originality/value: This research on the use of breadfruit flour as a partial substitute for wheat flour in making scones can be used as a reference to other studies which relate with the use of breadfruit flour and can be seen as an alternative substitution of wheat flour which is came from Indonesian local food ingredients. Breadfruit flour which is made into a rare but unique scone dish can also be used as a innovation or idea in business.